International Aspects of Budget Deficits with Distortionary Taxes. (IMF Working Papers; Working Paper, 1987)
Much of the recent research of the international economic consequences of budget deficit has been conducted under the assumption that taxes are lump sum. It has thus abstracted from important issues that arise in the context of distortionary tax systems. Our analysis deals with the international effects of budget deficits under alternative tax systems. The key result of the analysis is that the consequences of tax policies and the characteristics of the international transmission mechanism depend critically on the precise composition of taxes. Specifically, under a value-added tax system a budget deficit lowers the world rate of interest while under an income-tax system the same deficit raises the world rate of interest.